Disease understanding in patients newly diagnosed with atrial fibrillation. Issue 6 (8th August 2017) - Kaufman, Brystana G; Kim, Sunghee; Pieper, Karen; Allen, Larry A; Gersh, Bernard J; Naccarelli, Gerald V; Ezekowitz, Michael D; Fonarow, Gregg C; Mahaffey, Kenneth W; Singer, Daniel E; Chan, Paul S; Freeman, James V; et al.
Abstract : Objective: To describe self-reported disease understanding for newly diagnosed patients with atrial fibrillation (AF) and assess (1) how disease understanding changes over the first 6 months after diagnosis and (2) the relationship between patient understanding of therapies at baseline and treatment receipt at 6 months among treatment-naïve patients. Methods: We analysed survey data from SATELLITE (Survey of Patient Knowledge and Personal Priorities for Treatment), a substudy of patients with new-onset AF enrolled in the national Outcomes Registry for Better Informed Treatment of Atrial Fibrillation (ORBIT) II registry across 56 US sites. Patients were surveyed at the baseline and 6-month follow-up clinic visits using Likert scales. Results: Among 1004 baseline survey responses, patients' confidence in their understanding of rhythm control, ablation, anticoagulation and cardioversion was suboptimal, with 'high' understanding ranging from 8.5% for left atrial appendage closure to 71.3% for rhythm therapy. Of medical history and demographic factors, education level was the strongest predictor of reporting 'high' disease understanding. Among the 786 patients with 6-month survey data, significant increases in the proportion reporting high understanding were observed (p<0.05) only for warfarin and direct oral anticoagulants (DOACs). With the exception of ablation, high understanding for a given therapeutic option was not associated with increased use of that therapy at 6 months. Conclusions: About half of patients with new-onset AF understood the benefits of oral anticoagulant at the time of diagnosis and understanding improved over the first 6 months. However, understanding of AF treatment remains suboptimal at 6 months. Our results suggest a need for ongoing patient education. Clinical trial registration: Clinicaltrials.gov. Identifier: NCT01701817 .